Traumatic sacral fracture following dystocia in a Thoroughbred foal. (12th January 2017) - Mackenzie, C.; Haggett, E.; Powell, S.; Swarbrick, M.; Leaman, T.
Summary: A Thoroughbred colt with a history of dystocia was referred for further management of suspected hypoxia. The foal showed signs of neonatal maladjustment syndrome and hindlimb paralysis. Radiography revealed the presence of a severe lumbosacral injury. The foal was subjected to euthanasia due to a hopeless prognosis. Computed tomography was performed post‐mortem and revealed a type I Salter Harris fracture of the cranial physis of the first sacral vertebra.